COMPARISON OF MAGNETIC RESONANCE IMAGING AND MUTIDETECTOR COMPUTER TOMOGRAPHY FOR THE DIAGNOSIS OF MEDIASTINAL TUMORS - M, SURESH KUMAR (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: The aim of this study is to identify the diagnostic accuracy of mediastinal masses using multidetector computed tomography (MDCT) and magnetic resonance imaging (MRI). Method: A total of 30 cases were referred to the Department of Radiodiagnosis for clinically suspected mediastinal masses for 2 years were included and MDCT and MRI were done. Results: Lymphoma in 37.5% of cases, lymphoma and thymic masses in 31.25% of cases, Ca. esophagus and Schwannoma were the common mediastinal masses in the anterior, superior, middle, and posterior mediastinal compartments, respectively. MDCT sensitivity was 100% and MDCT specificity was 75%. MRI sensitivity was 100%, and MRI specificity was 80%. It was concluded that MDCT is a highly useful modality for the investigation of the mediastinal masses. It has the major role to play in the evaluation of a mediastinal mass regarding the organ of origin, its density, mass effect on adjacent structures, distribution pattern, and extent of the lesion diagnosis. MRI accurately well-characterized mediastinal mases such as thymoma, lymphoma, neurogenic tumor, Schwannoma, and ganglioneuroma. Conclusion: MRI was useful in the characterization of the normal thymus and differentiation of hyperplastic thymus and thymictumors